Low-shrinkage high-crack-resistance concrete and application thereof

By using highly water-absorbent materials as anti-cracking agents in large volume concrete, the self-shrinkage and cracking problems caused by the peak of hydration heat is solved, and the effects of low shrinkage and high crack resistance are achieved.

CN119707372AActive Publication Date: 2025-03-28CCCC FOURTH HARBOR ENG CO LTD +1

Patent Information

Application Number
CN202411903759.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The crack problems caused by temperature changes and shrinkage caused by large-volume concrete during hydration are difficult for the prior art to effectively control the generation and expansion of cracks.

Method used

Using highly water-absorbent materials as anti-cracking agents, by grafting hyperbranched polycarboxylic acid and bisacetone glucose polyacrylate into the concrete, small molecules that slowly release moisture and glucose are formed, reducing the peak of hydration heat, thereby reducing cracks caused by self-contraction.

Benefits of technology

It effectively reduces the self-shrinkage of large-volume concrete, reduces the generation and expansion of cracks, and improves the compressive strength and crack resistance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707372A_ABST
    Figure CN119707372A_ABST
Patent Text Reader

Abstract

Belonging to the technical field of concrete, the invention discloses a low shrinkage and high crack resistance concrete, which is prepared from the following raw materials by mix proportion: 130-160 kg / m < 3 > of cement, 50-70 kg / m < 3 > of fly ash, 50-70 kg / m < 3 > of mineral powder, 600-750 kg / m < 3 > of sand, 1300-1500 kg / m < 3 > of gravel, 3-5 kg / m < 3 > of a water reducer, 90-130 kg / m < 3 > of water, and 3-4 kg / m < 3 > of an anti-cracking agent. The anti-cracking agent is of a structure of cellulose grafted hyperbranched polycarboxylic acid and diacetone glucose polyacrylate, hydration heat release is slowly carried out through the dual effects of high water absorption and delayed coagulation, and the time needed by exchange of hydration heat and the environment is given; the anti-cracking agent has the advantages of good dispersity, small particle size, high water absorption and long slow release time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to low shrinkage and high crack resistance concrete and application thereof. Background Art

[0002] Mass concrete refers to concrete with a thickness, length and width of not less than 1m, or concrete that is expected to cause harmful cracks due to temperature changes and shrinkage caused by the hydration of cementitious materials in the concrete. After mass concrete is poured, a large amount of hydration heat is generated during its hardening and cement hydration process. The concrete is thick and large, and the exchange path between the hydration heat and the environment is long, resulting in uneven temperature distribution inside the structure. Since the heat inside the concrete is dissipated slowly, while the surface dissipates heat quickly, a large temperature difference between the inside and outside is formed, which leads to temperature stress on the surface of the concrete. When the temperature stress is greater than the tensile strength of the concrete at the same age, cracks are likely to form on the surface of the concrete. When the concrete gradually dissipates heat and cools and shrinks, due to the constraints, a large tensile stress will be generated at the contact point. When the tensile stress exceeds the ultimate tensile strength of the concrete at the same age, cracks will be generated at the contact point with the constraints, and may even penetrate the entire concrete block, causing serious quality accidents. Therefore, strict control should be exercised during the construction of mass concrete projects.

[0003] At present, there are several ways to control cracks in large-volume concrete: 1) optimize reinforcement, crack-resistant grid, shrinkage-compensating concrete, gradient concrete; 2) layered and block optimization, setting sliding layer, crack induction, preheating synergistic deformation; 3) low shrinkage and high crack resistance concrete, hydration heat inhibitor, thermal insulation and moisture maintenance, intelligent temperature control, etc. Highly absorbent materials have a low cross-linked three-dimensional network structure and have the ability to absorb and store several times their own dry weight in water solution. Highly absorbent materials can store water in concrete and release it again during the hydration process, thereby reducing the shrinkage caused by low water-cement ratio and self-drying of pores; and after the release of water, the polymer shrinks and retains the corresponding micropores in the microstructure, which plays a role in enhancing mechanical properties and crack resistance after air entrainment; it can also improve the impermeability of cracks by expanding and blocking cracks and promoting self-healing. The reinforcing effects of the above high-performance water-absorbing materials on concrete have been verified in the literature Journal of Building Engineering 51 (2022) 104219, Berlin. Beton- und Stahlbetonbau 119 (2024), Heft 7 and Cement and Concrete Composites 150 (2024) 105563. However, most of the high water-absorbing materials are cross-linked materials with large particle size. The particle size before water absorption is about 100 μm, which will have a certain impact on the mixing of cement, and the pores left behind are larger in particle size. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a low-shrinkage and high-crack-resistant concrete, wherein the anti-cracking agent is a structure of cellulose grafted hyperbranched polycarboxylic acid and diacetone glucose polyacrylate, and through the dual effects of high water absorption and slow setting, the hydration heat release is slowly carried out, giving the time required for the exchange of hydration heat and the environment; the anti-cracking agent is a highly water-absorbent material, which can be used as an internal water supply agent to store water in concrete and release it again during the hydration process, thereby reducing the self-shrinkage caused by low water-cement ratio and self-drying of pores.

[0005] The technical solution to achieve the purpose of the present invention is as follows: a low shrinkage and high crack resistance concrete, in terms of mix ratio, the raw materials include cement 130-160 kg / m 3 、Fly ash 50~70kg / m 3 、Mineral powder 50~70kg / m 3 , Sand 600~750kg / m 3 , Crushed stone 1300~1500kg / m 3 , water reducing agent 3~5kg / m 3 , Water 90~130kg / m 3 , Anti-cracking agent 3~4kg / m 3 ; The preparation method of the anti-cracking agent is as follows:

[0006] In an inert gas atmosphere, sodium carboxymethyl cellulose, carboxylic acid monomer, diacetone glucose monomer and peroxide are dispersed in an aqueous solution, and silver nitrate is dispersed in acetonitrile. After mixing, the mixture is stirred at 50-70° C. for 4-6 hours, vacuum filtered, and washed with ethanol and water at least twice in sequence. After filtering, the obtained solid is vacuum dried to obtain an anti-cracking agent.

[0007] The carboxylic acid monomer is at least one of methacrylic acid and acrylic acid; the diacetone glucose monomer has at least one of the following molecular structures of Formula I and Formula II:

[0008]

[0009] Preferably, the water is an ice-water mixture, and the ice content of the ice-water mixture is 50-70 kg / m 3 ; The peroxide is sodium persulfate.

[0010] Preferably, the content of sodium carboxymethyl cellulose in the aqueous solution is 1-2wt%; the content of the carboxylic acid monomer in the aqueous solution is 2-3wt%; the content of the diacetone glucose monomer in the aqueous solution is 0.5-1w.t%; the content of the peroxide in the aqueous solution is 2.5-3.5wt%; the content of the silver nitrate in acetonitrile is 0.05-0.25wt%; and the volume ratio of the aqueous solution to acetonitrile is 1:1.

[0011] Preferably, the carboxylic acid monomer is acrylic acid; the diacetone glucose monomer is the molecular structure of the above formula I; and the preparation method of the molecular structure of formula I is as follows:

[0012] In a reaction kettle, 1.0 eq of diacetone glucose is added and dissolved in dichloromethane, and then 2-3 eq of triethylamine is added and stirred under ice bath conditions. Using a constant pressure dropping funnel, 1.5-2.0 eq of acryloyl chloride diluted in 20-30 eq of dichloromethane is added dropwise into the above ice bath mixed solution under stirring conditions. After the dropwise addition is completed, the reaction solution is returned to room temperature and stirred for reaction for 10-12 hours. After the reaction is completed, it is washed with saturated sodium bicarbonate solution and distilled water at least twice in sequence, the organic phase is collected, the solvent is removed, and a colorless transparent oily liquid is obtained by purification and separation by column chromatography.

[0013] Preferably, the preparation method of the molecular structure of formula II is: replacing acryloyl chloride in the preparation method of formula I with methacryloyl chloride.

[0014] Preferably, a method for preparing low shrinkage and high crack resistance concrete comprises the following steps:

[0015] 1) Disperse the anti-cracking agent in water, with 1 kg of anti-cracking agent dispersed in 8-12 kg of normal temperature water;

[0016] 2) After the sand and gravel are precooled, cement, fly ash, mineral powder, are added into the sand and gravel cement mixer, stirred for 1 to 2 minutes, and then the ice-water mixture is added. After stirring for 2 to 5 minutes, the water reducer and the anti-cracking agent dispersed in water obtained in step 1) are added, and stirring is continued until the ice is fully melted and the concrete outlet temperature is ≤16°C;

[0017] 3) Concrete is poured in layers using a pump truck, with each layer of 30 to 50 cm evenly distributed. Concrete is vibrated using The vibrator is inserted into the concrete in a plum blossom pattern. The order of vibration is from the nearest formwork to the middle. The vibrator is inserted vertically into the concrete, and the lower layer is not less than 5 cm. Insert quickly and withdraw slowly, and vibrate up and down. The vibration time of each point is when the concrete surface shows cement slurry and no longer sinks and there is basically no bubbling on the surface.

[0018] 4) Water cooling, the horizontal spacing of cooling water pipes is 1.2-1.5m, the cooling water is controlled at 14℃-16℃, and the water flow rate is not less than 2.0m 3 / h, the cooling water direction is changed every 24 hours;

[0019] 5) Maintenance: thermal insulation and moisture retention of flat and inclined surfaces: after watering, cover with polymer water-saving and moisturizing maintenance film, and then cover with insulation board; vertical insulation and moisture retention: the vertical surface is covered with polymer water-saving and moisturizing maintenance film, insulation board or tarpaulin is hung on the outside for insulation, the structure is sealed with top insulation board, and the top is sprayed for maintenance, and the maintenance age is not less than 28d.

[0020] Beneficial Effects

[0021] The invention has the following beneficial effects: the invention adds a highly absorbent material as an anti-cracking agent into a large volume of concrete, and reduces the peak value of hydration heat by slowly releasing water and slowly releasing small glucose molecules to adsorb them on part of the cement, thereby reducing cracks caused by self-shrinkage caused by low water-cement ratio and pore self-drying; the highly absorbent material is obtained by grafting polycarboxylic acid and diacetone glucose onto hydroxymethyl cellulose. When the highly absorbent material is first added into cement and stirred, the main chain of the highly absorbent material is cellulose, and the side chains are linear or branched polycarboxyl and polydiacetone glucose in a comb-like structure, and the highly absorbent material has good dispersibility and certain water absorption capacity. As concrete is stirred in an alkaline environment, the external diacetone glucose is hydrolyzed to expose four hydroxyl groups, and the comb-like structure molecules are micro-cross-linked through hydrogen bonds. At this time, the well-dispersed highly absorbent material forms a three-dimensional network structure and the four hydroxyl structures provide storage capacity and hydrophilicity respectively, thereby further increasing the water absorption capacity; as the cement is hydrated, the temperature further increases, the glucose connected to the carboxyl group begins to hydrolyze, and after the hydrogen bond structure of the highly absorbent material is gradually removed, its water storage capacity begins to weaken and gradually releases water. The released glucose can be combined with cement as a retarder, further reducing the rate of cement hydration and reducing the peak value of hydration heat. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the structure of the flood discharge gate chamber in the mass concrete of the present invention;

[0023] Figure 2 The synthetic route and structural diagram of the anti-cracking agent of the present invention;

[0024] Figure 3 This is the NMR spectrum of the diacetone glucose monomer prepared by the present invention;

[0025] Figure 4 It is the infrared spectrum of sodium carboxymethyl cellulose and the anti-cracking agent of the present invention.

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0028] The raw materials and equipment used in the embodiments and comparative examples are described as follows:

[0029] Cement: medium heat Portland cement, P.MH 42.5, purchased from China Resources Cement;

[0030] Fly ash: fineness (45um square hole sieve residue) is 21.8%, Guodian Shenzhen Energy Huayingshan Power Generation Co., Ltd.;

[0031] Mineral powder: S95 mineral powder, purchased from Yangchun New Steel Co., Ltd., Xiangtan Steel Co., Ltd.;

[0032] Sand: Grade II medium sand, purchased from the urban area of ​​Liuzhou City;

[0033] Crushed stone: 5-20mm, 20-40mm, 40-80mm three-grade crushed stone, purchased from the urban area of ​​Liuzhou City;

[0034] Water reducing agent: polycarboxylic acid water reducing agent, Purchased from Jiangsu Subot;

[0035] Water: Liuzhou tap water, in line with the requirements of the standard "mixing water for concrete" (JGJ 63-2006);

[0036] Sodium carboxymethyl cellulose: viscosity 50-200 mPa.s, product number C299502, purchased from Shanghai Aladdin;

[0037] Acrylic acid: Product No. M102640, purchased from Shanghai Aladdin;

[0038] Diacetone glucose: Product No. 1036610, purchased from Shanghai Leyan;

[0039] Silver nitrate: Sinopharm Reagent;

[0040] Sodium persulfate: Sinopharm Reagent;

[0041] Ice crushing: flake ice unit, model FIP63E;

[0042] Chilled water: chiller, model LS-510;

[0043] Mixing station: HZS270-1Q4500 hydraulic mixing station;

[0044] Air-cooled aggregate system: Model AC600EPC;

[0045] Diacetone glucose monomer

[0046] In the reaction kettle, add 1.0eq of diacetone glucose and dissolve it in dichloromethane, then add 2.5eq of triethylamine, stir under ice bath conditions, use a constant pressure dropping funnel to dilute 2.0eq of acryloyl chloride in 30eq of dichloromethane, add the above ice bath mixed solution dropwise under stirring, after the addition is complete, return the reaction solution to room temperature, stir and react for 12h, after the reaction is completed, wash with saturated sodium bicarbonate solution and distilled water three times in sequence, collect the organic phase, remove the solvent, and purify and separate by column chromatography to obtain a colorless transparent oily liquid.

[0047] Anti-cracking agent 1

[0048] Under a nitrogen atmosphere, 1 g of sodium carboxymethyl cellulose, 2.5 g of acrylic acid, 0.5 g of diacetone glucose monomer and 3 g of sodium persulfate were dispersed in 100 ml of aqueous solution, and 0.05 g of silver nitrate was dispersed in 100 ml of acetonitrile. After mixing, the mixture was stirred at 60 °C for 5 h, vacuum filtered, washed with ethanol and water three times in sequence, filtered, and the obtained solid was vacuum dried to obtain anti-cracking agent 1.

[0049] Anti-cracking agent 2

[0050] Compared with the preparation method of anti-cracking agent 1, the difference is that 0.05g of silver nitrate is replaced by 0.10g.

[0051] Anti-cracking agent 3

[0052] Compared with the preparation method of anti-cracking agent 1, the difference is that 0.05g of silver nitrate is replaced by 0.15g.

[0053] Anti-cracking agent 4

[0054] Compared with the preparation method of anti-cracking agent 1, the difference is that 0.05g of silver nitrate is replaced by 0.20g.

[0055] Anti-cracking agent 5

[0056] Compared with the preparation method of anti-cracking agent 1, the difference is that 0.05g of silver nitrate is replaced by 0.25g.

[0057] Anti-cracking agent 6

[0058] Compared with the preparation method of the anti-cracking agent 1, the difference is that 0.5 g of diacetone glucose monomer is replaced by 0.5 g of acrylic acid.

[0059] Anti-cracking agent 7

[0060] Compared with the preparation method of the anti-cracking agent 1, the difference is that 2.5 g of acrylic acid is replaced by 2.5 g of diacetone glucose monomer.

[0061] Anti-cracking agent 8

[0062] 0.5 g of anti-cracking agent 1 was added and dissolved in 33 mL of dichloromethane, and then 15 mL of trifluoroacetic acid and 1.5 mL of water were added in sequence. The reaction was stirred for 24 h at room temperature. After the reaction was completed, dichloromethane was removed by rotary evaporation, and then an appropriate amount of water was added. The solution was precipitated in acetone several times until the solution was no longer acidic. The precipitate was separated by centrifugation and vacuum dried overnight to obtain the deprotected anti-cracking agent 8.

[0063] The following is the test method of the performance parameters involved in the present invention:

[0064] Determination of water absorption: accurately weigh 0.1g sample into a 500ml beaker, add 400ml deionized water, let stand at room temperature for 24h, wait until it reaches saturation, filter and let stand for 30min until no droplets fall, weigh the mass of the anti-cracking agent after swelling equilibrium, and calculate according to formula I:

[0065]

[0066] Q eq —Water absorption, unit: g·g -1 ;

[0067] M1—Total mass of gel and filter bag when saturated with water, in g;

[0068] M2—dry filter bag mass; unit: g;

[0069] M0—Dried sample mass, in g.

[0070] Anti-cracking agent length and rotation radius test: small angle neutron scattering test;

[0071] Temperature monitoring: The specimen size is 1000mm×1000mm×1000mm. According to JTS-T202-1-2022 "Overview of Technical Specifications for Temperature Crack Control of Mass Concrete in Water Transport Engineering", the internal and external temperatures of the concrete are monitored and calculated. Pre-embedded temperature measuring elements are used to directly reflect the internal temperature of the concrete casting body at the top, middle and bottom heights of the concrete. Nine measuring points are arranged from the surface to the inside of each layer, and a total of 27 measuring points are arranged on each level of the foundation to monitor the maximum temperature of the concrete and the temperature difference between the inside and the outside in real time.

[0072] Compressive strength: The specimen size is 150mm×150mm×150mm, and the test is carried out in accordance with the relevant provisions of standard GB / T50081-2019;

[0073] Cracks: Measure with standard point and line gauge, film ruler, comparison card and feeler gauge;

[0074] Air content: GB / T50080-2016 "Standard for test methods for properties of ordinary concrete mixtures".

[0075] Table 1 Characterization of anti-cracking agent performance

[0076] Anti-cracking agent 1 Anti-cracking agent 2 Anti-cracking agent 3 Anti-cracking agent 4 Anti-cracking agent 5 Anti-cracking agent 6 Anti-cracking agent 7 Anti-cracking agent 8 Length, nm ≥150 ≥150 ≥150 ≥150 ≥150 ≥150 ≥150 ≥150 Radius of rotation, nm 13.2 10.9 8.9 7.2 6.1 12.9 13.7 12.1 <![CDATA[Water absorption rate, g·g -1 > 62 173 263 142 51 73 31 397

[0077] From the data in Table 1, it can be seen that the lengths of anti-cracking agents 1 to 5 are basically the same because they use the same sodium carboxymethyl cellulose, but the radius of rotation gradually decreases. This is because as the content of the catalyst silver nitrate increases, the side groups of cellulose gradually transition from straight chains to branched chains, resulting in a decrease in length; as the degree of branching increases, the water absorption first increases and then decreases. At the beginning, the transformation from a linear structure to a branched structure can improve the water-locking ability of the anti-cracking agent, but as the branched structure further increases, water molecules are hindered from entering the branched structure, resulting in a decrease in water absorption. From the data of anti-cracking agents 6 to 8, it can be seen that the water absorption capacity of the acrylic acid group is better than that of unhydrolyzed diacetone glucose. When diacetone glucose is hydrolyzed and deprotected, its water absorption rate increases significantly. The hydrolysis of the external diacetone glucose exposes 4 hydroxyl groups, and the comb-like polymers are micro-crosslinked through hydrogen bonds. At this time, the three-dimensional network structure formed by the well-dispersed high water-absorbent material and the 4 hydroxyl structures provide water storage capacity and hydrophilicity, respectively, thereby further increasing the water absorption capacity.

[0078] A low-shrinkage and highly crack-resistant concrete refers to a thin-walled, large aspect ratio, and wide-section structure in a hub engineering structure. In a specific embodiment, the bottom plate size of the flood discharge gate is 35m×16.5m×2.6m, the gate pier casting block is 35m×1.75m×3m, the power station building bottom plate is 42m×29m×2.6m, the bottom plate size of the middle wall of the ship lock chamber is 32.8m×21.4m×1.5m, and the bottom plate size of the upper gate is 40m×23.5m×1.5m. The specific size can be adjusted according to the project situation or construction needs.

[0079] In a specific embodiment, the mass concrete is a laboratory specimen, and the specific size is a concrete structure of 1m×1m×1m.

[0080] A method for preparing low shrinkage and high crack resistance concrete comprises the following steps:

[0081] 1) Disperse the anti-cracking agent in water, 1 kg of anti-cracking agent in 10 kg of normal temperature water;

[0082] 2) Add cement, fly ash, mineral powder, sand and gravel into a cement mixer, stir for 2 minutes, then add ice-water mixture, stir for 5 minutes, add water reducer and anti-cracking agent dispersed in water obtained in step 1), continue stirring until the ice is fully melted and the concrete outlet temperature is ≤16°C;

[0083] 3) Concrete is poured in layers using a pump truck, with each layer of 40 cm evenly distributed, and concrete is vibrated using Insertion-type manual vibration, the vibration points are arranged in a plum blossom shape, and the vibration sequence starts from the near formwork to the middle. The vibrator is vertically inserted into the concrete, and the lower layer is not less than 5cm. Insert quickly and withdraw slowly, and pump up and down. The vibration time of each point is when the concrete surface shows cement slurry and no longer sinks and there is basically no bubbling on the surface;

[0084] 4) Water cooling, the horizontal spacing of cooling water pipes is 1.2m, the cooling water is controlled at 16℃, and the water flow rate is not less than 2.0m 3 / h, the cooling water direction is changed every 24 hours;

[0085] 5) Maintenance: thermal insulation and moisture retention of flat and inclined surfaces: after watering, cover with polymer water-saving and moisturizing maintenance film, and then cover with insulation board; vertical insulation and moisture retention: the vertical surface is covered with polymer water-saving and moisturizing maintenance film, insulation board or tarpaulin is hung on the outside for insulation, the structure is sealed with top insulation board, and the top is sprayed for maintenance, and the maintenance age is not less than 28d.

[0086] Table 2 Concrete formula of Examples 1 to 7 and Comparative Examples 1 to 5 (unit: kg / m 3 )

[0087]

[0088]

[0089] Table 3 Concrete performance test

[0090]

[0091] It can be seen from the data in Table 3 that the maximum temperature difference of Examples 1 to 7 is less than 20°C, the compressive strength is greater than 45Mpa, and there are no visible cracks. It can be seen from the data of Comparative Example 1 that not adding the anti-cracking agent prepared by the present invention will lead to a large temperature difference and cracks. It can be seen from the data of Comparative Example 2 that adding too much anti-cracking agent prepared by the present invention will lead to a decrease in compressive strength, which is due to the generation of bubbles caused by too much anti-cracking agent. It can be seen from Comparative Examples 3 to 5 that the carboxylic acid and diacetone glucose structures in the anti-cracking agent of the present invention play a complementary role, and the effect of a single component is not excellent. Among them, the strength of Comparative Examples 4 and 5 is relatively low. It is speculated that the dispersibility of 7 to 8 is poor, resulting in the generation of too many harmful pores with larger pore sizes.

[0092] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low shrinkage and high crack resistance concrete, characterized in that: In terms of mix ratio, the raw materials include cement 130-160 kg / m 3 、Fly ash 50~70kg / m 3 、Mineral powder 50~70kg / m 3 , Sand 600~750kg / m 3 , Crushed stone 1300~1500kg / m 3 , water reducing agent 3~5kg / m 3 , Water 90~130kg / m 3 , Anti-cracking agent 3~4kg / m 3 ; The preparation method of the anti-cracking agent is as follows: In an inert gas atmosphere, sodium carboxymethyl cellulose, carboxylic acid monomer, diacetone glucose monomer and peroxide are dispersed in an aqueous solution, silver nitrate is dispersed in acetonitrile, mixed and stirred at 50-70° C. for 4-6 hours, vacuum filtered, washed with ethanol and water at least twice in sequence, filtered, and the obtained solid is vacuum dried to obtain an anti-cracking agent; The carboxylic acid monomer is at least one of methacrylic acid and acrylic acid; the diacetone glucose monomer has at least one of the following molecular structures of Formula I and Formula II:

2. A low shrinkage and high crack resistance concrete as claimed in claim 1, characterized in that: The water is an ice-water mixture, and the ice content of the ice-water mixture is 50-70 kg / m 3 ; The peroxide is sodium persulfate.

3. The low shrinkage and high crack resistance concrete according to claim 1, characterized in that: The content of sodium carboxymethyl cellulose in the aqueous solution is 1-2wt%; the content of the carboxylic acid monomer in the aqueous solution is 2-3wt%; the content of the diacetone glucose monomer in the aqueous solution is 0.5-1wt%; the content of the peroxide in the aqueous solution is 2.5-3.5wt%; the content of the silver nitrate in acetonitrile is 0.05-0.25wt%; and the volume ratio of the aqueous solution to acetonitrile is 1:

1.

4. The low shrinkage and high crack resistance concrete according to claim 1, characterized in that: The carboxylic acid monomer is acrylic acid; the diacetone glucose monomer is a molecular structure of formula I; the preparation method of the molecular structure of formula I is as follows: In a reaction kettle, 1.0 eq of diacetone glucose is added and dissolved in dichloromethane, and then 2-3 eq of triethylamine is added and stirred under ice bath conditions. Under stirring conditions, 1.5-2.0 eq of acryloyl chloride diluted in 20-30 eq of dichloromethane is added dropwise to the above ice bath mixed solution using a constant pressure dropping funnel. After the dropwise addition is completed, the reaction solution is returned to room temperature and stirred for reaction for 10-12 hours. After the reaction is completed, it is washed with saturated sodium bicarbonate solution and distilled water at least twice in sequence, the organic phase is collected, the solvent is removed, and a colorless transparent oily liquid is obtained by purification and separation by column chromatography.

5. A method for preparing low shrinkage and high crack resistance concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Disperse the anti-cracking agent in water, with 1 kg of anti-cracking agent dispersed in 8-12 kg of normal temperature water; 2) Add cement, fly ash, mineral powder, sand and gravel into a cement mixer, stir for 1 to 2 minutes, then add ice-water mixture, stir for 2 to 5 minutes, add water reducer and anti-cracking agent dispersed in water obtained in step 1), continue stirring until the ice is fully melted and the concrete outlet temperature is ≤16°C; 3) Concrete is poured in layers using a pump truck, with each layer of 30 to 50 cm evenly distributed. Concrete is vibrated using Insertion-type manual vibration, the vibration points are arranged in a plum blossom shape, and the vibration sequence starts from the near formwork to the middle. The vibrator is vertically inserted into the concrete, and the lower layer is not less than 5cm. Insert quickly and withdraw slowly, and pump up and down. The vibration time of each point is when the concrete surface shows cement slurry and no longer sinks and there is basically no bubbling on the surface; 4) Water cooling, the horizontal spacing of cooling water pipes is 1.2-1.5m, the cooling water is controlled at 14℃-16℃, and the water flow rate is not less than 2.0m 3 / h, the cooling water direction is changed every 24 hours; 5) Maintenance: thermal insulation and moisture retention of flat and inclined surfaces: after watering, cover with polymer water-saving and moisturizing maintenance film, and then cover with insulation board; vertical insulation and moisture retention: the vertical surface is covered with polymer water-saving and moisturizing maintenance film, insulation board or tarpaulin is hung on the outside for insulation, the structure is sealed with top insulation board, and the top is sprayed for maintenance, and the maintenance age is not less than 28d.

6. Application of the low shrinkage and high crack resistance concrete as claimed in any one of claims 1 to 4 in flood discharge gate chambers, power station building floors, ship lock chamber middle wall floors, and upper gate head floors.

Citation Information

Patent Citations

  • Novel self-healing cement mortar and preparation method thereof

    CN116655293A

  • Non-shrinkage anti-cracking low-carbon concrete for rigid waterproofing

    CN116768543A

  • Shrinkage-reducing anti-cracking mass concrete and preparation method thereof

    CN117585963A

  • Internally curing cement based materials

    US20110073015A1

Cited By

  • Low-shrinkage, high-crack-resistance and low-carbon concrete based on low-carbon cementing material and preparation method of low-shrinkage, high-crack-resistance and low-carbon concrete

    CN121318318A